Prevalence and risk factors of enteral nutrition intolerance in intensive care unit patients: a retrospective study. Issue 15 (5th August 2022) - Yu, Kunrong; Guo, Na; Zhang, Dingding; Xia, Ying; Meng, Yanling; Weng, Li; Du, Bin
Abstract: Background: Feeding intolerance (FI) among intensive care unit (ICU) patients undergoing early continuous enteral nutrition (EN) is related to poor outcomes. This study aimed to explore the prevalence and risk factors of FI in ICU patients. Methods: We retrospectively enrolled 1057 patients who received early continuous EN via a nasogastric tube between January 2014 and August 2019. The prevalence of FI during the first 7 days of ICU stay was calculated, and the risk factors were investigated using multivariate logistic regression analysis. Results: The prevalence of FI during the first 7 days of ICU stay was 10.95%. FI occurred in 159 of 1057 (15.04%) patients on ICU day 2, 114 of 977 (11.67%) patients on ICU day 3, and 86 of 715 (12.03%) patients on ICU day 7. Mechanical ventilation (MV) (odds ratio [OR]: 1.928, 95% confidence interval [CI]: 1.064–3.493, P  = 0.03) was an independent risk factor for FI defined by a gastric residual volume (GRV) of 200 mL and/or vomiting, and acute renal failure (OR: 3.445, 95% CI: 1.115–10.707, P  = 0.032) was an independent risk factor of FI defined by a GRV of 500 mL and/or vomiting. Continuous renal replacement therapy (CRRT) was an independent predictor regardless of the FI defined by a GRV of 200 mL (OR: 2.064, 95% CI: 1.233–3.456, P  = 0.006) or 500 mL (OR: 6.199, 95% CI: 2.108–18.228, P  = 0.001) in the ICU patients. Conclusions: FI occurs frequently in early ICU days, especially in patients receiving MV and CRRT. However, further investigation of a consensus definition of FI and risk factors is still warranted in future studies.